2019
DOI: 10.3846/jeelm.2019.9315
|View full text |Cite
|
Sign up to set email alerts
|

Torrefaction of Oil Palm Fronds (Opf) as a Potential Feedstock for Energy Production Processes

Abstract: Oil palm fronds (OPF) and trunks contribute the highest biomass availability compared with other oil palm wastes. At the moment, they are usually left on the ground around the plantation area to decompose naturally and fertilize the soil. Previous researchers have focused on torrefaction of wood residues and other agricultural biomass with less attention has been paid to the utilization of Malaysia’s biomass such as OPF. Therefore, in this study, torrefaction of OPF was conducted in a tubular reactor at temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The effect of torrefaction temperature on the torrefied OPF performance seem to be dominant compared to the other parameters. This can be found when the torrefaction temperature is increased, the HHV of torrefied OPF is enhanced (19.3 to 29.22 MJ/kg) [5,6,8,9,12,13,26,27], carbon content (44.5 to 56.68%) [5,7,8]) and fixed carbon content (12.68 to 57.1%) [7,8,13,26,27] of torrefied OPF also increases.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The effect of torrefaction temperature on the torrefied OPF performance seem to be dominant compared to the other parameters. This can be found when the torrefaction temperature is increased, the HHV of torrefied OPF is enhanced (19.3 to 29.22 MJ/kg) [5,6,8,9,12,13,26,27], carbon content (44.5 to 56.68%) [5,7,8]) and fixed carbon content (12.68 to 57.1%) [7,8,13,26,27] of torrefied OPF also increases.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have reported that raw OPF can be potentially upgraded to become a promising energy source similar to empty fruit bunch (EFB), palm kernel shell (PKS), and mesocarp fibre (MSF). This is due to its significant amount of carbon content, which typically ranges from 40.30 to 48.43% [1,[3][4][5][6][7][8][9]. In the energy production, the amount of energy (known as higher heating value, HHV) that can be produced during the combustion of a fuel is vital [10], along with other requirements such as conversion efficiency, pollutant emissions, etc [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oil palm frond and trunk contribute the highest biomass availability compared with other oil palm waste (Thaim, Rasid, & Wan Ismail, 2019). Pruning of frond and leaflet has become a necessity and routinely carry out in oil palm plantations to facilitate maintenance and harvesting.…”
Section: Introductionmentioning
confidence: 99%